2016
DOI: 10.1080/14737140.2017.1272414
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine therapy in epithelial ovarian cancer

Abstract: Introduction:The estrogen receptor (ER) is expressed at high levels in many epithelial ovarian cancers (EOC) and represents a potential target for endocrine therapy. Both anti-estrogens and aromatase inhibitors have been evaluated in phase II clinical trials. Areas covered:We present an overview of the phase II and phase III trials of anti-estrogens (tamoxifen and fulvestrant) and aromatase inhibitors (letrozole, anastrazole and exemestane) undertaken in epithelial ovarian cancer identified through a Pubmed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…In ovarian cancer samples, androstenedione can be formed from DHEA (Chura et al, 2009a), although Ren et al (Ren et al, 2015) found no evidence for further formation of estrogens via the aromatase pathway or activation of androstenedione to testosterone and 5α-dihydrotestosterone, as also supported by down-regulation of AKR1C3 . However, in other studies, CYP19A1 was expressed in stroma cells of ovarian cancers (Manna et al, 2016), and has been considered a target for an endocrine therapy (Langdon et al, 2017). …”
Section: Disturbed Transport and Estrogen Actions In Gynecological Camentioning
confidence: 98%
“…In ovarian cancer samples, androstenedione can be formed from DHEA (Chura et al, 2009a), although Ren et al (Ren et al, 2015) found no evidence for further formation of estrogens via the aromatase pathway or activation of androstenedione to testosterone and 5α-dihydrotestosterone, as also supported by down-regulation of AKR1C3 . However, in other studies, CYP19A1 was expressed in stroma cells of ovarian cancers (Manna et al, 2016), and has been considered a target for an endocrine therapy (Langdon et al, 2017). …”
Section: Disturbed Transport and Estrogen Actions In Gynecological Camentioning
confidence: 98%
“…However, the clinical activity of endocrine therapy in ovarian cancer has been disappointing, with response rates reminiscent of many tested therapeutic agents that have been deemed inactive . Small phase 2 studies have shown response rates of the AI letrozole in recurrent ovarian cancer to be 0%‐15% (Table ) . Despite low response rates to aromatase inhibition, clinical benefit rates (responses plus stable disease) of letrozole are estimated to be as high as 56% with duration of disease stability of 9.6 months .…”
Section: Use Of Endocrine Therapy In the Treatment Of Ovarian Cancer?mentioning
confidence: 99%
“…[87][88][89] Small phase 2 studies have shown response rates of the AI letrozole in recurrent ovarian cancer to be 0%-15% (Table 3). 88,90 Despite low response rates to aromatase inhibition, clinical benefit rates (responses plus stable disease) of letrozole are estimated to be as high as 56% with duration of disease stability of 9.6 months. 91 Several clinical trials of the SERM tamoxifen (Table 3) have demonstrated an overall 10%-13% objective response rate and a 32%-35% disease stabilization rate.…”
Section: Use Of Endocrine Therapy In the Treatment Of Ovarian Cancer?mentioning
confidence: 99%
“…Despite numerous published clinical studies on the effectiveness and safety of ET in EOC during the past decades the role of ET in EOC is not well defined [4][5][6][7][8][9][10]. We do not know which hormonal agent is most effective nor the optimal setting.…”
Section: Introductionmentioning
confidence: 99%
“…histological subtypes) and includes mainly heavily pretreated patients. Despite the low evidence for efficacy, ET is an attractive treatment option, and included in many international guidelines for heavily pretreated patients, since it is associated with an often-favourable safety profile, easy intake and low cost [5,7,[9][10][11]15]. Patient preference is important in the decision-making process of choosing best treatment, especially at late relapse, but must be based on thorough physician-patient communication including information regarding prognosis and treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%